India's war : the making of modern South Asia, 1939-1945 - Raghavan, Srinath (New Delhi: Penguin Books, 2016)
"Between 1939 and 1945 India underwent extraordinary and irreversible change. Hundreds of thousands of Indians suddenly found themselves in uniform, fighting in the Middle East, North and East Africa, Europe, and against a Japanese army poised to invade eastern India. In India's War, historian Srinath Raghavan paints a compelling picture of battles abroad and life on the home front, arguing that the war is crucial to understanding how and why colonial rule ended in South Asia,"--NoveList.
"First published in 2016 by Allen Lane"--Title-page verso.
Keywords: World War, 1939-1945 -- India; World War, 1939-1945 -- Participation, East Indian; War and society -- India -- History -- 20th century